Effect of Indole Acetic Acid on Wheat (Triticum aestivum L.) Irrigated with Sewage Water - K.Sagar1 and J.N. Maurya1*, Chandra Shekhar Kumar1, Alka Singh2, R. (Journal of Phytology, 2011)
A field experiment was conducted to study the accumulation of heavy metals by winter wheat (Triticum aestivum L.) variety PBW-343 grown under sewage water (collected from Harun Nagla channel of Bareilly city, U.P., India.) of two different concentrations (50% and 100%). Effects of indole-3- acetic acid (IAA) of two different concentrations (10ppm and 20ppm) were applied after 25, 50, 75 and 100days of seed germination. The quantities of heavy metals like Pb, Cr, Zn, Cu and Fe were determined at physiological maturity in wheat plant. Indole-3- acetic acid treatment alleviated the adverse effect of toxic heavy metals contents of sewage water due to production of enzymatic and non-enzymatic antioxidants like superoxide dismutase (SOD), catalase (CAT), glutathione reductase (GR), carotenoids, and proline respectively, and enhanced the plant growth and yield of wheat. The 100% concentration of sewage water with 20ppm of Indole-3- acetic acid showed decrease in uptake of heavy metals like Cr, Pb whereas an increase in Zn, Cu, Fe uptake was noticed with 10ppm of Indole-3- acetic acid and 100% concentration of sewage water by wheat grains.